Botulinum Toxin Use in the Lower Urinary Tract - Shelby N. Morrisroe; Michael B. Chancellor (The Scientific World Journal)
Botulinum toxins are well known for their ability to disrupt neurotransmission and cause muscle paralysis. Recently, urologists have discovered their beneficial effects in patients with neurogenic and overactive bladder conditions. This review is intended to provide a quick overview for urologists of the structure, function, and clinical uses of botulinum neurotoxin A in the lower urinary tract.